2017
DOI: 10.1186/s40734-017-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Indirect tolerability comparison of Deutetrabenazine and Tetrabenazine for Huntington disease

Abstract: BackgroundVesicular monoamine transporter 2 (VMAT2) inhibitors can improve hyperkinetic movements, and are effective treatment options for chorea of Huntington disease (HD). Tetrabenazine was assessed for treating chorea in the TETRA-HD trial, and while efficacious, there are tolerability concerns possibly due to its pharmacokinetic properties. Deutetrabenazine is a novel VMAT2 inhibitor that contains deuterium, which extends active metabolite half-lives and minimizes drug concentration fluctuations. In the Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 24 publications
1
59
0
1
Order By: Relevance
“…Deutetrabenazine contains a deuterium atom and is a novel inhibitor of VMAT2. In indirect treatment comparison studies, deutetrabenazine was found to have a favorable tolerability profile compared to tetrabenazine [41]. In mouse models, TBZ ameliorated chorea and other motor symptoms, and reduced striatal neuronal cell loss [38].…”
Section: Tetrabenazine (Tbz) and Deutetrabenazinementioning
confidence: 99%
“…Deutetrabenazine contains a deuterium atom and is a novel inhibitor of VMAT2. In indirect treatment comparison studies, deutetrabenazine was found to have a favorable tolerability profile compared to tetrabenazine [41]. In mouse models, TBZ ameliorated chorea and other motor symptoms, and reduced striatal neuronal cell loss [38].…”
Section: Tetrabenazine (Tbz) and Deutetrabenazinementioning
confidence: 99%
“…Comparing deutetrabenazine with tetrabenazine for the treatment of TD using meta‐analytic techniques is not possible as there are no randomised placebo‐controlled studies of tetrabenazine for TD; however, in an indirect comparison of deutetrabenazine and tetrabenazine for Huntington's disease, tetrabenazine and deutetrabenazine did not differ significantly on motor scores or adverse events, but depression and somnolence scales favoured deutetrabenazine significantly . Another indirect analysis comparing tolerability of deutetrabenazine and tetrabenazine in Huntington's disease demonstrated that deutetrabenazine was associated with a significantly lower risk of moderate to severe adverse events and neuropsychiatric adverse events including agitation, akathisia, depression, depression/agitated depression, drowsiness/somnolence, insomnia and parkinsonism; deutetrabenazine also had a significantly lower rate of dose reduction or dose reduction/suspension …”
Section: Discussionmentioning
confidence: 99%
“…There are two other VMAT2 inhibitors on the market: tetrabenazine (3-times daily) and deutatrabenazine (twice-daily), both of them approved by FDA for chorea associated with HD. Apart from dosage regimen, it is unclear if there are differences between these two modestly effective drugs, which have comparable safety profiles with risks of suicidality, parkinsonism and QT prolongation [10][11][12].…”
Section: Sponsors/funders: Neurocrine Biosciences and The Huntington mentioning
confidence: 99%